A Hybrid Measurement Approach to Medium Occupied Time for Radio Resource Management in IEEE 802.11 Networks. (3rd May 2015) - Yang, Seung-Chur; Kim, Jong-Deok
Abstract : The wireless resources required by users have increased in parallel with and above improvements in WLAN technology, requiring even more accurate and practical resource management. Research on medium utilization, which is fundamental to resource management, has supplied insufficient evidence to apply it in real environments. This paper proposes a hybrid measurement approach to medium utilization using both a signal-level register monitor and a frame-level frame parser. We redefine medium utilization in terms of Medium Occupied Time (MOT) to describe the status of the medium in more detail. The proposed approach enables us to measure the classified MOT occupied by 802.11 frames, wireless interference, and a MAC protocol. We implement our approach by modifying a Linux device driver of an off-the-shelf 802.11n NIC. In addition, an indoor test bed is built to verify the approach's support for various traffic patterns, quantitative measurement of wireless interference, and backoff time estimation. We conclude that our hybrid measurement approach is accurate and deployable in a real environment.